2020
DOI: 10.1080/0886022x.2020.1853569
|View full text |Cite
|
Sign up to set email alerts
|

Elevated atherogenic index and higher triglyceride increase risk of kidney function decline: a 7-year cohort study in Chinese adults

Abstract: Objective: This study explored whether lipid disorders or an elevated atherogenic index of plasma (AIP, a risk factor for cardiovascular diseases) could predict major kidney function decline. Methods: We conducted a retrospective 7-year cohort study of 3712 Chinese adults followed up between 2010 and 2017. Major kidney function decline was defined as a ! 30% reduction in the estimated glomerular filtration rate (eGFR) from baseline. Multivariable logistic regression models were used to evaluate the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“… 36 Additionally, TG can be a predictor of decline in renal function. 37 , 38 In our study, better glycemic control (HbA1c = 7.3%) had no influence on the presence of microalbuminuria, since this correlation has been found with higher HbA1c values (>10.5%). 39 …”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“… 36 Additionally, TG can be a predictor of decline in renal function. 37 , 38 In our study, better glycemic control (HbA1c = 7.3%) had no influence on the presence of microalbuminuria, since this correlation has been found with higher HbA1c values (>10.5%). 39 …”
Section: Discussionsupporting
confidence: 43%
“…36 Additionally, TG can be a predictor of decline in renal function. 37,38 In our study, better glycemic control (HbA1c = 7.3%) had no influence on the presence of microalbuminuria, since this correlation has been found with higher HbA1c values (>10.5%). 39 Our results demonstrated that HDL-c, microalbuminuria ≥30 mg and the presence of carotid disease were associated with the development of stroke.…”
Section: Discussionmentioning
confidence: 44%
“…AIP is often used to assess the degree of atherosclerosis and to predict the severity of lipid metabolism disorders beyond individual lipids and/or TC/HDL-C ratios. Several studies have confirmed the association of AIP with metabolic syndrome, carotid plaque, and renal insufficiency, among others [ 25 , 26 ]. Additionally, recent studies have shown that AIP is a strong marker for predicting the risk of atherosclerosis and cardiovascular disease, and cardiovascular disease risk factors are related to the integrity of brain structures and cognitive impairment [ 27 ].…”
Section: Discussionmentioning
confidence: 85%
“…Firstly, decreased lipase and downregulation of lipoprotein receptors in patients with dyslipidemia and renal impairment affect the normal metabolism of very low density lipoprotein (VLDL) and chylomicrons, ultimately leading to an accumulation of TG and an increased risk of atherosclerotic complications [ 29 ]. Moreover, results of long-term cohort studies showed that higher serum TG levels increased the risk of severe decline in renal function, even in healthy individuals [ 30 , 31 ]. Based on the above evidence, TG is not only an important indicator for patients with advanced CKD, but also plays a role in predicting early CKD.…”
Section: Discussionmentioning
confidence: 99%